LEGAL PROTECTION FOR DOCTOR AND MEDICAL STAFF IN THE PANDEMIC PERIOD OF COVID-19 (An Overview of Indonesia from International Perspective) - Ong Argo Victoria; Thaan Neet Bunprakop (UNISSULA, 2020)
When first announced as a global pandemic on March 11 by WHO the number of infections worldwide has reached more than 121,000. Instead of Indonesia still feeling safe from a virus outbreak that has paralyzed some countries in the world, President Joko Widodo in early March, who had put the population in a comfort zone, had to admit defeat with a co-19 case report caused by the virus SARS-Cov-2 or better known as the Corona virus. Even with the dynamism of existing data, these predictions can change. This data is certainly not to create panic in the community, but rather to make people aware and provide an overview for the government in handling it. Namely comprehensive handling, especially to prevent wider spread so that the number of infections can be suppressed. In addition, legal certainty is an important instrument in ensuring the safety of health workers so that the government cannot take arbitrary actions against the assignment of health workers. Especially if you look at the legislation regarding health workers, it seems that no one has yet regulated the guarantee of legal certainty for health workers even though Law Number 36 of 2014 concerning Health Workers is already in place. Therefore the Government needs to issue implementing regulations and technical guidelines for the Health Workforce Law and other laws governing legal protection and work safety for health workers. In line with this, Chairman of the Indonesian Lung Doctors Association AgusDwi Susanto, announced that the number of lung specialist doctors is limited, this must be sought by the government with further grouping of funds so that the number of cases of infection does not overwhelm health workers, this is done to break the chain of viral circulation with the help of partially quarantine and social procurement.